El CROSSFIT y su relación con el Vo2 máximo en jóvenes adultos - Rosero Becerra, Jonathan Stalin (2023)
The following research presents results about the increase of VO2 due to the practice of CrossFit, this research was developed around young adults aged between 20 and 40 years, taking into account that these people had a sedentary life, the sample to study was made up of both male and female. This research was carried out for three consecutive months, where a pre-test was applied to show the changes suffered during the trial period; the participants developed the CrossFit exercises for forty-five minutes daily, considering his training practice was Monday through Friday. The COURSE NAVETTE was taken into consideration for data collection, which is a test that allows the researcher to obtain significant data for the final comparison. The entire investigation process was carried out at the Reino Fitness gym located in the city of Riobamba in the province of Chimborazo. To better cement the research product, a process of information collection was carried out using different search engines, which helped to establish a theoretical margin that contributed to the development of decision-making, as in the interpretation of the data obtained.